Effectiveness of anti-vascular endothelial growth factors in neovascular age-related macular degeneration and variables associated with visual acuity outcomes: Results from the EAGLE study. - Giovanni Staurenghi (Public Library of Science (PLoS), 2021)
Objective To assess the overall effectiveness of anti-vascular endothelial growth factor (VEGF) therapy in treatment-naïve patients with neovascular age-related macular degeneration (nAMD) in a clinical practice setting. Study design EAGLE was a retrospective, 2-year, cohort observational, multicenter study conducted in Italy that analyzed secondary data of treatment-naïve patients with nAMD. The primary endpoint evaluated the mean annualized number of anti-VEGF injections at Years 1 and 2. The main secondary endpoints analyzed the mean change in visual acuity (VA) from baseline and variables associated with visual outcomes at Years 1 and 2. Results Of the 752 patients enrolled, 745 (99.07%) received the first dose of anti-VEGF in 2016. Overall, 429 (57.05%) and 335 (44.5%) patients completed the 1- and 2-year follow-ups, respectively. At baseline, mean (standard deviation, SD) age was 75.6 (8.8) years and the mean (SD) VA was 53.43 (22.8) letters. The mean (SD) number of injections performed over the 2 years was 8.2 (4.1) resulting in a mean (SD) change in VA of 2.45 (19.36) (P = 0.0005) letters at Year 1 and -1.34 (20.85) (P = 0.3984) letters at Year 2. Linear regression models showed that age, baseline VA, number of injections, and early fluid resolution were the variables independently associated with visual outcomes at Years 1 and 2. Conclusions The EAGLE study analyzed the routine clinical practice management of patients with nAMD in Italy. The study suggested that visual outcomes in clinical practice may be improved with earlier diagnosis, higher number of injections, and accurate fluid resolution targeting during treatment induction.